Global epidemiology of severe fever with thrombocytopenia syndrome virus in human and animals: a systematic review and meta-analysisResearch in context - Haoliang Cui; Shijing Shen; Lin Chen; Zhiyu Fan; Qian Wen; Yiwen Xing; Zekun Wang; Jianyi Zhang; Jingyuan Chen; Bin La; Yujie Fang; Zeping Yang; et al. (Elsevier, 2024)
Summary: Background: Since the initial identification of the Severe Fever with Thrombocytopenia Syndrome (SFTS) in ticks in rural areas of China in 2009, the virus has been increasingly isolated from a diverse array of hosts globally, exhibiting a rising trend in incidence. This study aims to conduct a systematic analysis of the temporal and spatial distribution of SFTS cases, alongside an examination of the infection rates across various hosts, with the objective of addressing public concerns regarding the spread and impact of the disease. Methods: In this systematic review and meta-analysis, an exhaustive search was conducted across multiple databases, including PubMed, Web of Science, Embase, and Medline, CNKI, WanFang, and CQVIP. The literature search was confined to publications released between January 1, 2009, and May 29, 2023. The study focused on collating data pertaining to animal infections under natural conditions and human infection cases reported. Additionally, species names were unified using the National Center for Biotechnology Information (NCBI) database. The notification rate, notification death rate, case fatality rate, and infection rates (or MIR) were assessed for each study with available data. The proportions were pooled using a generalized linear mixed-effects model (GLMM). Meta-regressions were conducted for subgroup analysis. This research has been duly registered with PROSPERO, bearing the registration number CRD42023431010. Findings: We identified 5492 studies from database searches and assessed 238 full-text studies for eligibility, of which 234 studies were included in the meta-analysis. For human infection data, the overall pooled notification rate was 18.93 (95% CI 17.02-21.05) per ten million people, the overall pooled notification deaths rate was 3.49 (95% CI 2.97-4.10) per ten million people, and the overall pooled case fatality rate was 7.80% (95% CI 7.01%-8.69%). There was an increasing trend in notification rate and deaths rate, while the case fatality rate showed a significant decrease globally. Regarding animal infection data, among 94 species tested, 48 species were found to carry positive nucleic acid or antibodies. Out of these, 14 species were classified under Arthropoda, while 34 species fell under Chordata, comprising 27 Mammalia and 7 Aves. Interpretation: This systematic review and meta-analysis present the latest global report on SFTS. In terms of human infections, notification rates and notification deaths rates are on the rise, while the case fatality rate has significantly decreased. More SFTSV animal hosts have been discovered than before, particularly among birds, indicating a potentially broader transmission range for SFTSV. These findings provide crucial insights for the prevention and control of SFTS on a global scale. Funding: None.